Reinforced microcrystalline glass as well as preparation method and application thereof
By introducing lithium-permeable feldspar and lithium disilicate into the microcrystalline glass and chemically strengthening treatment to form a specific stress layer structure, the problem of insufficient anti-fall performance of existing microcrystalline glass is solved, and the effect of significantly improving the anti-fall performance is achieved. It is suitable for protective cover materials for high-end mobile phones.
Patent Information
- Application Number
- CN202411812732.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-22
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-07-22
AI Technical Summary
The existing microcrystalline glass has insufficient anti-fall performance, making it difficult to meet the performance needs of mid-to-high-end mobile phones.
By introducing lithosparish and lithium disilicate as the main crystal phase into the microcrystalline glass and undergoing chemical reinforcement treatment, a compressive stress layer and a tensile stress layer are formed to meet specific stress characteristics.
The anti-falling performance of microcrystalline glass is significantly improved, making its average anti-sandpaper drop height reach 1.30~1.80m in the 80-mesh sandpaper drop test, and is suitable for protective cover material for high-end mobile phones.
Smart Images

Figure CN119683860A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium aluminum silicon glass-ceramics, and in particular to a glass-ceramic with excellent drop resistance and a preparation method thereof. This invention patent application is a divisional application of the invention patent application with application number 202210869057.X, application date July 22, 2022, and invention name “A strengthened glass-ceramic and its preparation method and application”. Technical Background
[0002] With the advent of the smart phone era, mobile phones have become an indispensable communication tool in daily life. As the number of mobile phone users increases year by year, in order to meet the requirements of mobile phone users and increase the user experience, the speed of mobile phone updates, changes and elimination is also increasing. Mobile phones are becoming thinner and lighter, and the performance requirements for their cover glass are gradually increasing. Among them, microcrystalline glass with petalite and lithium disilicate as the main crystal phases can achieve a crystallinity of more than 70wt%, and the transmittance in the 360-740nm light band is close to that of commonly used lithium aluminum silicate glass. It can also be chemically strengthened with a salt bath to further improve its mechanical properties such as drop resistance and impact resistance. Therefore, it stands out and has received widespread attention from the cover industry.
[0003] The reason why cover glass breaks during use is usually that it falls from a high place, causing the glass to collide with sharp objects (such as fine sand, cement, and pebbles). The glass surface is partially damaged, and microcracks are formed at the damage point. The cracks extend from the glass surface to the inside. When the cracks extend through the depth of the compressive stress layer on the glass surface to reach the tensile stress layer area, the cracks will rapidly expand in the tensile stress area, causing the cracks to penetrate the entire glass, thereby causing the glass to be damaged and broken.
[0004] The existing patent is a microcrystalline glass with petalite and lithium disilicate as the main crystal phases, which mainly inhibits crack propagation by increasing CT and DOL_0 after strengthening to improve the glass's anti-destructive performance.
[0005] CN201980020541.1 obtains the absolute value of the maximum surface compressive stress through a specific strengthening method, which is 1.8 to 2.2 times the absolute value of the maximum central tensile stress, and the maximum CT value reaches 140MPa.
[0006] CN202010348413.4 uses two-step mixed salt strengthening to make the maximum CT reach 120MPa, DOL_0≥100μm, and the maximum tensile stress linear density reach 50000MPa / mm. Summary of the invention
[0007] However, the drop resistance of these glasses is still insufficient and it is difficult to meet the performance requirements of current mid-to-high-end mobile phones.
[0008] In view of the problem that the drop resistance of the microcrystalline glass in the prior art is difficult to meet the demand, the inventors have conducted extensive research and provided a microcrystalline glass with better drop resistance, which has significantly improved drop resistance compared with the prior art.
[0009] Specifically, the present invention provides the following technical solutions:
[0010] 1. A strengthened glass-ceramic, wherein the strengthened glass-ceramic contains a petalite crystal phase and a lithium disilicate crystal phase, and the strengthened glass-ceramic has a compressive stress layer formed by chemical strengthening on the surface and a tensile stress layer inside;
[0011] The strengthened glass-ceramics meets the following requirements:
[0012] DOL_0≥0.187t, t is the thickness of the strengthened glass-ceramics;
[0013] 1.01%≥Δα≥0.65%, Δα=5×10 -5 ×|CT_AV|+0.0026;
[0014] (CS_50 / DOL_0)≥0.332×(surface CS / |CT_CV|);
[0015] in:
[0016] Surface CS: surface compressive stress, in MPa;
[0017] CS_50: compressive stress at a depth of 50 μm from the glass surface, in MPa;
[0018] CT_AV: absolute value of average tensile stress in the tensile stress layer, in MPa;
[0019] CT_CV: maximum tensile stress in the tensile stress layer, in MPa; and
[0020] DOL_0: Depth of compressive stress layer, in μm.
[0021] 2. The strengthened glass-ceramics according to technical solution 1, wherein the tensile stress layer of the strengthened glass-ceramics contains the following percentages of oxides by weight:
[0022] SiO2: 65.00~75.00%,
[0023] Al2O3: 5.00~10.00%,
[0024] P2O5: 1.00~5.00%,
[0025] CaO: 0.10~3.00%,
[0026] ZrO2: 1.00~10.00%,
[0027] Na2O: 0~5.00%,
[0028] Li2O: 5.00~15.00%,
[0029] K2O: 0.10-3.00%, and
[0030] B2O3: 0~4.00%.
[0031] 3. The strengthened glass-ceramics according to technical solution 1, wherein the tensile stress layer of the strengthened glass-ceramics contains the following percentages of oxides by weight:
[0032] SiO2: 68.00~72.00%,
[0033] Al2O3: 5.00~10.00%,
[0034] P2O5: 1.00~3.00%,
[0035] CaO: 0.10~1.00%,
[0036] ZrO2: 2.00~8.00%,
[0037] Na2O: 0~1.00%,
[0038] Li2O: 8.00~13.00%,
[0039] K2O: 0.10-1.00%, and
[0040] B2O3: 0~2.00%.
[0041] 4. The strengthened glass-ceramics according to technical solution 1, wherein the tensile stress layer of the strengthened glass-ceramics contains the following percentages of oxides by weight:
[0042] SiO2: 70.00~72.00%,
[0043] Al2O3: 6.00~8.00%,
[0044] P2O5: 1.50~3.00%,
[0045] CaO: 0.50~1.00%,
[0046] ZrO2: 5.00~7.00%,
[0047] Na2O: 0.05~0.60%,
[0048] Li2O: 9.00~12.00%,
[0049] K2O: 0.10-0.50%, and
[0050] B2O3: 0.10~1.00%.
[0051] 5. The strengthened glass-ceramics according to technical solution 1, wherein the tensile stress layer of the strengthened glass-ceramics contains the following percentages of oxides by weight:
[0052] SiO2: 70.06~71.65%,
[0053] Al2O3: 7.24~7.43%,
[0054] P2O5: 2.49~2.83%,
[0055] CaO: 0.77~0.98%,
[0056] ZrO2: 5.40~6.11%,
[0057] Na2O: 0.06~0.31%,
[0058] Li2O: 11.10~11.95%,
[0059] K2O: 0.13~0.37% and
[0060] B2O3: 0.21~0.91%.
[0061] 6. The strengthened glass-ceramics according to Technical Solution 1, wherein the total content of the petalite crystal phase and the lithium disilicate crystal phase in the strengthened glass-ceramics is greater than 75 wt%.
[0062] 7. The tempered glass-ceramics according to any one of technical solutions 1 to 6, wherein, at a thickness of 0.7 mm, an 80-mesh sandpaper is used to perform a sandpaper drop resistance test on the tempered glass-ceramics, and the average sandpaper drop resistance height of the tempered glass-ceramics is 1.30 to 1.80 m.
[0063] 8. The strengthened microcrystalline glass according to any one of technical solutions 1 to 6, wherein, at a thickness of 0.7 mm, for light of a wavelength of 550 nm, the strengthened microcrystalline glass is transparent and has a transmittance of not less than 90.00%.
[0064] 9. The method for preparing the strengthened glass-ceramics according to any one of technical solutions 1 to 8 is characterized by comprising the following steps:
[0065] (1) Preparation of substrate glass: After mixing various glass raw materials, adding a clarifier, melting and forming, and annealing to obtain the substrate glass;
[0066] (2) Preparation of glass-ceramics: subjecting the substrate glass obtained in step (1) to nucleation treatment and crystallization treatment to obtain glass-ceramics;
[0067] (3) cold working the glass-ceramics obtained in step (2) to obtain a polished sheet; and
[0068] (4) The polished sheet obtained in step (3) is subjected to chemical strengthening treatment to obtain strengthened microcrystalline glass.
[0069] 10. The preparation method according to technical solution 9, wherein in step (1), the annealing temperature is 450-600°C, preferably 450-550°C, and the annealing time is 6-240 hours, preferably 6-120 hours. Annealing is divided into four stages: heating, heat preservation, slow cooling, and fast cooling. Theoretically, at a certain temperature, the longer the annealing time, the less residual stress. However, considering the time cost, the time should not be too long. Sample bricks of different specifications require different annealing times to reduce the thermal stress of the sample bricks to a usable range. The larger the size of the sample brick, the longer the required annealing time.
[0070] 11. The preparation method according to technical solution 9 or 10, wherein in step (2), when the nucleation treatment is performed, the nucleation temperature is 500-700°C, preferably 540-570°C, and the nucleation treatment time is preferably 10-1440 min.
[0071] 12. The preparation method according to technical solution 11, wherein, in step (2), when performing nucleation treatment, the temperature is increased to the nucleation temperature at a heating rate of 5 to 20°C / min, preferably at a heating rate of 10°C / min.
[0072] 13. The preparation method according to technical solution 9 or 10, wherein, in step (2), when the crystallization treatment is carried out, the crystallization temperature is 640-750°C, preferably 660-740°C, or 670-740°C, and the preferred crystallization treatment time is 5-1440 min.
[0073] 14. The preparation method according to technical solution 13, wherein, in step (2), when performing crystallization treatment, the temperature is increased to the crystallization temperature at a heating rate of 5 to 20°C / min, preferably at a heating rate of 10°C / min.
[0074] 15. The preparation method according to technical solution 9 or 10, wherein in step (4), the polishing sheet obtained in step (3) is chemically strengthened in a pure sodium salt or lithium sodium potassium mixed salt bath at 380 to 550° C., and the strengthening time is preferably 1 to 24 hours.
[0075] 16. The preparation method according to technical solution 15, wherein in step (4), the sodium ions in the salt bath are provided by any one or more of sodium nitrate, sodium sulfate and sodium carbonate, the potassium ions are provided by any one or more of potassium nitrate, potassium sulfate and potassium carbonate, and the lithium ions are provided by one or more of lithium nitrate, lithium sulfate and lithium carbonate.
[0076] 17. A preparation method according to technical solution 15 or 16, wherein the composition of the lithium-sodium-potassium mixed salt bath is: in terms of mass ratio, it contains 0.1-100wt% NaNO3 and 0-99.9wt% KNO3, and contains 0-10wt% LiNO3 relative to the total mass of NaNO3 and KNO3.
[0077] 18. A preparation method according to technical solution 15 or 16, wherein the composition of the lithium-sodium-potassium mixed salt bath is: in terms of mass ratio, it contains 30-95wt% NaNO3 and 5-70wt% KNO3, and contains 0.01-1wt%, preferably 0.01-0.1wt% LiNO3 relative to the total mass of NaNO3 and KNO3.
[0078] 19. According to the preparation method described in technical solution 15, the chemical strengthening treatment in the step (4) is carried out 1 to 3 times.
[0079] 20. According to the preparation method of technical solution 9 or 10, in the step (1), the clarifier is selected from any one or more substances selected from the group consisting of NaCl, Sb2O3, As2O3, nitrates, and sulfates, and the mass ratio of the clarifier added to the glass is preferably 0.10-1.00wt%, and more preferably 0.50-1.00wt%; and / or
[0080] In the step (1), the melt molding is performed at 1400 to 1650°C.
[0081] 21. The strengthened microcrystalline glass obtained by the preparation method described in any one of Technical Solutions 9-20.
[0082] 22. Use of the tempered glass-ceramics described in any one of Technical Solutions 1 to 8 or the tempered glass-ceramics described in Technical Solution 21 as a protective cover in a mobile device.
[0083] The stress characteristics of the strengthened microcrystalline glass provided by the present invention satisfy 1.01%≥Δα≥0.65% (Δα=5×10 -5×|CT_AV|+0.0026), (CS_50 / DOL_0)≥0.332×(surface CS / |CT_CV|), DOL_0≥0.187t, under the condition of 80-grit sandpaper, the average height of the sandpaper drop resistance can reach 1.30-1.80m. The drop resistance of the tempered microcrystalline glass on rough ground is significantly improved compared with the prior art, and can be used as a protective cover material for smart terminal products such as mobile phones. BRIEF DESCRIPTION OF THE DRAWINGS
[0084] Figure 1 is a DSC graph of the substrate glass in Example 3 of the present invention, which is heated to 1000° C. at a rate of 10° C. / min in nitrogen;
[0085] Figure 2 is a transmittance curve of the glass-ceramics of Example 3 of the present invention at 200nm to 1000nm;
[0086] Figure 3 is the X-ray diffraction pattern of the glass-ceramics of Example 3 of the present invention;
[0087] Figure 4 It is a schematic diagram of the tempered microcrystalline glass of the present invention falling and breaking. DETAILED DESCRIPTION
[0088] In order to solve the problem of poor drop resistance of microcrystalline glass in the prior art, the present invention provides a transparent microcrystalline glass with petalite and lithium disilicate as main crystal phases, which can be chemically strengthened to obtain strengthened microcrystalline glass. The strengthened microcrystalline glass has a compressive stress layer formed by chemical strengthening on the surface and a tensile stress layer inside. Since the tensile stress layer has not undergone ion exchange, its composition is the same as that of the transparent microcrystalline glass before strengthening.
[0089] The strengthened glass-ceramics meets the following stress characteristics:
[0090] DOL_0≥0.187t, t is the thickness of glass-ceramics;
[0091] 1.01%≥Δα≥0.65%, Δα=5×10 -5 ×|CT_AV|+0.0026;
[0092] (CS_50 / DOL_0)≥0.332×(surface CS / |CT_CV|);
[0093] Δα is a function that is positively correlated with the absolute value of the average tensile stress. When Δα>1.01% in the tempered microcrystalline glass, the tensile stress of the microcrystalline glass product is too large, which will cause the microcrystalline glass to self-explode. When Δα<0.65%, the tensile stress of the microcrystalline glass product is small and the drop resistance is poor.
[0094] (CS_50 / DOL_0) / (surface CS / |CT_CV|) is the comprehensive relationship between surface compressive stress, central tensile stress and stress layer depth. When (CS_50 / DOL_0) is less than 0.332×(surface CS / |CT_CV|), when the glass comes into contact with sharp objects, microcracks are easily generated and expand inward, resulting in a decrease in the glass's anti-drop performance.
[0095] DOL_0 is the depth of the compressive stress layer (referred to as "compressive stress layer depth"). When DOL_0 < 0.187t, the compressive stress layer is relatively shallow. When the glass comes into contact with sharp objects, the cracks generated are more likely to penetrate the compressive stress layer and reach the tensile stress zone, thereby reducing the glass's drop resistance.
[0096] In the present invention, those skilled in the art can select the thickness of the strengthened glass-ceramics according to the requirements. For example, in some embodiments, the thickness of the strengthened glass-ceramics is 0.2-2.0 mm. The thickness change of the glass-ceramics before and after chemical strengthening is very small and can be ignored.
[0097] The composition range of the strengthened glass-ceramics of the present invention is that the tensile stress layer of the strengthened glass-ceramics contains the following percentages of oxides, calculated by weight:
[0098] SiO2: 65.00~75.00%
[0099] Al2O3: 5.00~10.00%
[0100] P2O5: 1.00~5.00%
[0101] CaO: 0.10~3.00%
[0102] ZrO2: 1.00~10.00%
[0103] Na2O: 0~5.00%
[0104] Li2O: 5.00~15.00%
[0105] K2O: 0.10~3.00%
[0106] B2O3: 0~4.00%.
[0107] Preferably, the tensile stress layer of the strengthened glass-ceramics contains the following percentages of oxides:
[0108] SiO2: 68.00-72.00%, preferably 70.00-72.00%
[0109] Al2O3: 5.00-10.00%, preferably 6.00-8.00%
[0110] P2O5: 1.00~3.00%, preferably 1.50~3.00%
[0111] CaO: 0.10-1.00%, preferably 0.50-1.00%
[0112] ZrO2: 2.00-8.00%, preferably 5.00-7.00%
[0113] Na2O: 0-1.00%, preferably 0.05-0.60%
[0114] Li2O: 8.00-13.00%, preferably 9.00-12.00%
[0115] K2O: 0.10-1.00%, preferably 0.10-0.50%
[0116] B2O3: 0~2.00%, preferably 0.10~1.00%.
[0117] Further preferably, the tensile stress layer of the strengthened glass-ceramics contains the following percentages of oxides:
[0118] SiO2: 70.06~71.65%,
[0119] Al2O3: 7.24~7.43%,
[0120] P2O5: 2.49~2.83%,
[0121] CaO: 0.77~0.98%,
[0122] ZrO2: 5.40~6.11%,
[0123] Na2O: 0.06~0.31%,
[0124] Li2O: 11.10~11.95%,
[0125] K2O: 0.13~0.37% and
[0126] B2O3: 0.21~0.91%.
[0127] In the strengthened microcrystalline glass of the present invention, the total content of the petalite crystal phase and the lithium disilicate crystal phase accounts for more than 75wt% of the strengthened microcrystalline glass, preferably greater than or equal to 79wt%, and more preferably greater than or equal to 80wt%. It is accompanied by possible impurities, such as quartz, spodumene, lithium metasilicate, etc. Lithium disilicate Li2Si2O5 is an orthorhombic crystal, which is often flat and has a distinct dissociation surface. Due to its irregular orientation, this crystal phase forces cracks to extend along the distorted grain boundary, reducing the possibility of crack extension. 10 It is a monoclinic crystal, Li and O are tetrahedral coordination, and petalite can be chemically strengthened in a salt bath. The Na + Substituting Li in petalite + .
[0128] In some embodiments, the total content of the petalite crystalline phase and the lithium disilicate crystalline phase contained in the strengthened microcrystalline glass of the present invention is 79wt% to 97wt%. In some embodiments, the total content of the petalite crystalline phase and the lithium disilicate crystalline phase contained in the strengthened microcrystalline glass of the present invention is 79wt%, 80.00wt%, 81.00wt%, 82.00wt%, 83.00wt%, 84.00wt%, 85.00wt%, 86.00wt%, 87.00wt%, 88.00wt%, 89.00wt%, 90.00wt%, 91.00wt%, 92.00wt%, 93.00wt%, 94.00wt%, 95.00wt%, 96.00wt% or 97.00wt%. Or any proportion within the numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as needed, as long as the glass with the desired properties of the present invention can be obtained.
[0129] In some embodiments, in the strengthened glass-ceramics, the average size of the grains is 10nm-50nm, preferably 10nm-30nm, and more preferably 10nm-20nm. In some embodiments, the average size of the grains can be 10nm, 12nm, 14nm, 16nm, 18nm, 20nm, 22nm, 24nm, 26nm, 28nm, 30nm, 35nm, 38nm, 40nm, 45nm, 48nm or 50nm, or any ratio within the numerical range formed by any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as needed, as long as the glass-ceramics of the present invention can be obtained.
[0130] The strengthened microcrystalline glass according to the present invention also has the following stress characteristics:
[0131] Surface CS: 200~680MPa;
[0132] CS_50: 100~400MPa;
[0133] CS_100: 20~150MPa;
[0134] |CT_CV|: 50~210MPa;
[0135] |CT_AV|: 55~150MPa;
[0136] CT_LD: 45000~90000MPa / mm.
[0137] Strengthened glass-ceramic's drop resistance / fall resistance:
[0138] At a thickness of 0.7 mm, the tempered glass-ceramics provided by the present invention was subjected to a sandpaper drop resistance test using 80-mesh sandpaper. The average sandpaper drop resistance height of the tempered glass-ceramics was 1.30 to 1.80 m.
[0139] At a thickness of 0.7 mm, the strengthened microcrystalline glass provided by the present invention was subjected to a sandpaper drop resistance test using 120-mesh sandpaper. The average sandpaper drop resistance height of the strengthened microcrystalline glass was greater than 2.00 m.
[0140] At a thickness of 0.7 mm, the strengthened microcrystalline glass provided by the present invention was subjected to a sandpaper drop resistance test using 180-mesh sandpaper. The average sandpaper drop resistance height of the strengthened microcrystalline glass was greater than 2.50 m.
[0141] Strengthening the optical properties of glass-ceramics:
[0142] The transmittance of the strengthened microcrystalline glass under the wavelength of 200-1000nm is tested. Figure 2 As shown. Figure 2 It can be seen that the tempered microcrystalline glass has a high transmittance and good transparency in the visible light wavelength.
[0143] At a thickness of 0.7 mm, the strengthened microcrystalline glass is transparent to light with a wavelength of 550 nm and has a transmittance of not less than 90.00%.
[0144] The present invention prepares microcrystalline glass with a high crystal content by ceramicizing lithium aluminum silicate glass, and then places the microcrystalline glass in pure sodium salt or lithium sodium potassium mixed salt for chemical strengthening, so that the glass meets the above-mentioned stress requirements after strengthening and obtains better anti-drop performance.
[0145] SiO2 is an oxide that forms the glass network and is an indispensable component of the glass network structure. Properly increasing the content of SiO2 can increase the stability and mechanical strength of the glass, but excessive SiO2 will increase the viscosity of the glass, causing the problem of difficulty in melting the glass. Therefore, when the SiO2 content is controlled at 65.00-75.00wt%, it is best to increase the stability and formability of the glass. In some embodiments, the weight percentage of SiO2 is 68.00%-72.00%. In some embodiments, the weight percentage of SiO2 is 70.00%-72.00%. In some embodiments, the weight percentage of SiO2 is 70.06%-71.65%. In some embodiments, the tensile stress layer of the strengthened microcrystalline glass may include 65.00% to 71.00%, 66.00% to 71.00%, 67.00% to 71.00%, 68.00% to 71.00%, 68.00% to 69.50%, 67.00% to 69.50%, 68.00% to 71.00%, 67.30% to 71.00%, 67.50% to 71.00%, 67.70% to 71.00%. 1.00%, 68.20% to 71.00%, 68.50% to 71.00%, 68.80% to 71.00%, 69.00% to 71.00%, 69.00% to 69.80%, 69.00% to 69.50%, 69.00% to 69.30%, 69.50 to 70.00%, 70.00 to 70.50%, 71.00 to 71.50% or 71.50 to 72.00% SiO2. In some embodiments, the tensile stress layer of the strengthened microcrystalline glass may include 65.00%, 66.00%, 67.00%, 67.10%, 67.20%, 67.30%, 67.40%, 67.50%, 67.60%, 67.70%, 67.80%, 67.90%, 68.00%, 68.10%, 68.20%, 68.30%, 68.40%, 68.50%, 68.60%, 68.70%, 68.80%, 68.90%, 69.00%, 69.10%, 69.20%, 69.30%, 69.40%, 69.50%, 69.60%, 69.70%, 69.80%, 69.90%, 71.00%, 72.00%, 73.00%, 74.00% or 75.00% SiO2, or SiO2 in a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0146] Al2O3 is an intermediate oxide in the formation of glass, which can improve the chemical stability of glass. At the same time, since [AlO4] is larger in volume than [SiO4], it can provide more space for ion exchange, so aluminum oxide can promote ion exchange. However, excessive Al2O3 tends to increase the viscosity of the glass, and when alkaline earth metals are present, it will also increase the tendency of glass crystallization. Therefore, the Al2O3 content is controlled at 5.00-10.00wt%. In some embodiments, the weight percentage of Al2O3 can be 6.00-8.00%. In some embodiments, the weight percentage of Al2O3 can be 7.24-7.43%. In some embodiments, the tensile stress layer of the strengthened microcrystalline glass may include 5.00%, 5.30%, 5.50%, 5.80%, 6.00%, 6.30%, 6.50%, 6.80%, 7.00%, 7.30%, 7.50%, 7.80%, 8.00%, 8.30%, 8.50%, 8.80%, 9.00%, 9.30%, 9.50%, 9.80% or 10.00% Al2O3 by weight, or Al2O3 within a numerical range formed by any two of the above specific numerical values as endpoints. It should be understood that, in the embodiments, any of the above ranges may be combined with any other ranges.
[0147] P2O5 can act as a glass network forming oxide and promotes glass phase separation, thereby affecting the crystallization of the glass. In the transparent microcrystalline glass of the Li2O-Al2O3-SiO2 system, the P2O5 content is controlled at 1.00-5.00wt%. In some embodiments, the weight percentage of P2O5 can be 1.00-3.00%; in some embodiments, the weight percentage of P2O5 can be 1.50-3.00%; in some embodiments, the weight percentage of P2O5 can be 2.49-2.83%; in some embodiments, in the tensile stress layer of the strengthened microcrystalline glass, 1.00%, 1.20%, 1.50%, 1.70%, 1.80%, 2.00%, 2.20%, 2.50%, 2.80%, 3.00%, 3.20%, 3.50%, 3.80%, 4.00%, 4.20%, 4.50%, 4.80% or 5.00% of P2O5 can be included by weight, or P2O5 within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in the embodiments, any of the above ranges can be combined with any other ranges.
[0148] ZrO2 is an intermediate oxide in the formation of glass. It can improve the chemical stability of glass, increase the hardness of glass, and increase the scratch and drop resistance of glass. At the same time, ZrO2 has a large accumulation effect on the glass structure due to its high cationic charge and strong field strength. It is often used as a nucleating agent in microcrystalline glass. However, excessive ZrO2 will greatly increase the viscosity of the glass and affect the forming ability of the glass. The ZrO2 content in the transparent microcrystalline glass of the Li2O-Al2O3-SiO2 system is controlled to be 1.00-10.00wt%. In some embodiments, the weight percentage of ZrO2 can be 2.00% to 8.00%; in some embodiments, the weight percentage of ZrO2 can be 5.00% to 7.00%; in some embodiments, the weight content of ZrO2 can be 5.40% to 6.11%; in some embodiments, the tensile stress layer of the strengthened microcrystalline glass can contain 1.00%, 1.20%, 1.40%, 1.60%, 1.80%, 2.00%, 2.20%, 2.40%, 2.60%, 2.80%, 3.00%, 3.20%, 3.40%, 3.60%, 3.80%, 4. %. .00%, 4.20%, 4.40%, 4.60%, 4.80%, 5.00%, 5.20%, 5.40%, 5.60%, 5.80%, 6.00%, 6.20%, 6.40%, 6.60%, 6.80%, 7.00%, 7.20%, 7.40%, 7.60%, 7.80%, 8.00%, 8.20%, 8.40%, 8.60%, 8.80%, 9.00%, 9.20%, 9.40%, 9.6%, 9.8% or 10.0% ZrO2, or ZrO2 in a numerical range consisting of any two of the above specific numerical values as endpoints. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0149] CaO, as a network exo-oxide formed by glass, helps to reduce the viscosity of glass, inhibits glass crystallization during glass forming, and can also improve the low-temperature melting property of glass. However, excessive CaO will reduce the resistance to devitrification of glass. By adding an appropriate amount of CaO, the viscosity of glass can be reduced without affecting the crystallization performance of glass. Therefore, the present application controls the content of CaO to be 0.10-3.00wt%. In some embodiments, the weight percentage of CaO can be 0.10-1.00%. In some embodiments, the weight percentage of CaO can be 0.50-1.00%. In some embodiments, the weight percentage of CaO can be 0.77-0.98%. In some embodiments, the tensile stress layer of the strengthened glass-ceramics may include 0.10%, 0.15%, 0.18%, 0.20%, 0.25%, 0.28%, 0.30%, 0.35%, 0.38%, 0.40%, 0.45%, 0.48%, 0.50%, 0.55%, 0.58%, 0.60%, 0.65%, 0.68% by weight. %, 0.70%, 0.75%, 0.78%, 0.80%, 0.85%, 0.88%, 0.90%, 0.95%, 0.98%, 1.00%, 1.50%, 1.75%, 2.00%, 2.25%, 2.50%, 2.75% or 3.00% CaO, or CaO in a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0150] Li2O, Na2O, and K2O, as the external oxides of the glass network, can improve the viscosity of the glass and promote the melting and clarification of the glass liquid. At the same time, Li2O and Na2O can also exchange ions with the molten salt bath. The content of the two is an important factor affecting the stress of the glass. In addition, Li2O is also a lithium disilicate (Li2Si2O5), lithium metasilicate (Li2SiO3) and petalite (LiAlSi4O 10 ) are necessary chemical components for the formation of crystalline phases. However, the free oxygen provided by Li2O, Na2O, and K2O will destroy the network structure of the glass and affect the intrinsic strength of the glass. Therefore, the present application controls the content of Li2O to be 5.00-15.00wt%, the content of Na2O to be 0-5.00wt%, and the content of K2O to be 0.10-3.00wt%.
[0151] In some embodiments, the Li2O content is controlled within the range of 8.00-13.00 wt %; in some embodiments, the Li2O content is controlled within the range of 9.00-12.00 wt %; in some embodiments, the Li2O content is controlled within the range of 11.10-11.95 wt %.
[0152] In some embodiments, the tensile stress layer of the strengthened glass-ceramics may include 5.00%, 5.50%, 6.00%, 6.50%, 7.00%, 7.50%, 8.00%, 8.10%, 8.15%, 8.20%, 8.25%, 8.30%, 8.35%, 8.40%, 8.45%, 8.50%, 8.55%, 8.60%, 8.65%, 8.70%, 8.75%, 8.80%, 8.85%, 8.90%, 8.95%, 8.90%, 8.95%, 8.96%, 8.97%, 8.98%, 8.99%, 8.10%, 10.15%, 10.20%, 10.25%, 10.30%, 10.40%, 10.50%, 10.60%, 10.75%, 10.80%, 10.98%, 10.99%, 10.10%, 10.15%, 10.20%, 10.25%, 10.30%, 10.35%, 10.40%, 10.50%, 10.60%, 10.75%, 10.80%, 10. .00%, 9.10%, 9.15%, 9.20%, 9.25%, 9.30%, 9.35%, 9.40%, 9.45%, 9.50%, 9.55%, 9.60%, 9.65%, 9.70%, 9.75%, 9.80%, 9.85%, 9.90%, 9.95%, 10.00%, 10.10%, 10.15%, 10.20%, 10.25%, 10.30%, 10.35%, 10.40%, 10.45%, 10.50%, 10.55%, 10.60 %, 10.65%, 10.70%, 10.75%, 10.80%, 10.85%, 10.90%, 10.95%, 11.00%, 11.10%, 11.15%, 11.20%, 11.25%, 11.30%, 11.35%, 11.40%, 11.45%, 11.50%, 11.55%, 11.60%, 11.65%, 11.70%, 11.75%, 11.80%, 11.85%, 11.90%, 11.95%, 12.00%, 12. %, 12.15%, 12.20%, 12.25%, 12.30%, 12.35%, 12.40%, 12.45%, 12.50%, 12.55%, 12.60%, 12.65%, 12.70%, 12.75%, 12.80%, 12.85%, 12.90%, 12.95%, 13.00%, 13.50%, 14.00%, 14.50% or 15.00% Li2O, or Li2O in a numerical range consisting of any two of the above specific numerical values as endpoints. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0153] In some embodiments, the Na2O content is controlled at 0.01-1.00 wt%; in some embodiments, the Na2O content is controlled at 0.05-0.60 wt%; in some embodiments, the Na2O content is controlled at 0.06-0.31 wt%.
[0154] In some embodiments, the tensile stress layer of the strengthened glass-ceramics may include 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0 %, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.5 3%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0. %. 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 1.00%, 2.00%, 3.00%, 4.00% or 5.00% Na2O, or Na2O in a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0155] In some embodiments, the K2O content is controlled within the range of 0.10 to 1.00 wt %; in some embodiments, the K2O content is controlled within the range of 0.10 to 0.50 wt %.
[0156] In some embodiments, in the tensile stress layer of the strengthened microcrystalline glass, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30% by weight may be included. , 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56% , 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82% %, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 1.00%, 2.00% or 3.00% K2O, or K2O within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0157] B2O3, as a flux in the glass formation process, can reduce the high temperature viscosity of the glass, accelerate the clarification of the glass, and reduce the crystallization ability of the glass. However, excessive B2O3 will reduce the chemical stability and mechanical strength of the glass. Therefore, the B2O3 content is controlled to be 0-4.00wt%. In some embodiments, the B2O3 content is controlled to be 0-2.00%. In some embodiments, the B2O3 content is controlled to be 0.10-1.00%. In some embodiments, the B2O3 content is controlled to be 0.21-0.91%. In some embodiments, the tensile stress layer of the strengthened glass-ceramics may include 0.10%, 0.15%, 0.18%, 0.20%, 0.25%, 0.28%, 0.30%, 0.35%, 0.38%, 0.40%, 0.45%, 0.48%, 0.50%, 0.55%, 0.58%, 0.60%, 0.65%, 0.68%, 0.70%, 0.75%, 0.78%, 0.80%, 0.85%, 0.88%, 0.90%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 100%, 101%, 102%, 103%, 104%, 105%, 106%, 107%, 108%, 109%, 110%, 111%, 112%, 113%, 114%, 115%, 116%, 117%, 118%, 119%, 120%, 121%, 122%, 123%, 124%, 125%, 126%, 127%, 128%, 129%, 130%, 131%, 132%, 133%, 134%, 135%, 136%, 137%, 138%, 139%, 140%, 141%, 142%, 143%, 144%, 145%, 146%, 147%, 148%, 149%, 150%, 151%, 152%, 153%, 154%, 155%, %, 0.98%, 1.00%, 1.10%, 1.15%, 1.18%, 1.20%, 1.25%, 1.28%, 1.30%, 1.35%, 1.38%, 1.40%, 1.45%, 1.48%, 1.50%, 1.55%, 1.58%, 1.60%, 1.65%, 1.68%, 1.70%, 1.75%, 1.78%, 1.80%, 1.85%, 1.88%, 1.90%, 1.95%, 1.98%, 2.00%, 2.1 0%, 2.15%, 2.18%, 2.20%, 2.25%, 2.28%, 2.30%, 2.35%, 2.38%, 2.40%, 2.45%, 2.48%, 2.50%, 2.55%, 2.58%, 2.60%, 2.65%, 2.68%, 2.70%, 2.75%, 2.78%, 2.80%, 2.85%, 2.88%, 2.90%, 2.95%, 2.98%, 3.00%, 3.10%, 3.15%, 3.18%, 3. %, 20%, 3.25%, 3.28%, 3.30%, 3.35%, 3.38%, 3.40%, 3.45%, 3.48%, 3.50%, 3.55%, 3.58%, 3.60%, 3.65%, 3.68%, 3.70%, 3.75%, 3.78%, 3.80%, 3.85%, 3.88%, 3.90%, 3.95%, 3.98% or 4.00% B2O3, or B2O3 in a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0158] Terminology explanation:
[0159] Base glass: glass that has not been subjected to nucleation, crystallization and strengthening treatments.
[0160] Glass-ceramics: also known as glass ceramics, is a type of solid composite material that contains both glass phase and crystal phase (microcrystalline phase, crystalline phase) and is prepared by targeted and controlled crystallization of the base glass.
[0161] Nucleation: Through heat treatment, the nucleating material in the glass grows small crystal nuclei.
[0162] Crystallization: Glass grows a certain crystal based on the crystal nucleus through heat treatment.
[0163] Crystalline phase: Crystalline phase is the microscopic structure of crystals, which is a general term for parts composed of a large number of crystalline solid phases.
[0164] CT_LD: tensile stress line density, the ratio of the sum of tensile stresses of the tempered glass-ceramics measured by the SLP-2000 stress meter to the glass thickness.
[0165] The glass-ceramics is placed in a salt bath for ion exchange to form a compressive stress layer (i.e., a strengthening layer), and a tensile stress layer is formed inside the glass during the ion exchange process. Specifically, during chemical strengthening, ions with a large radius in the salt bath are exchanged with ions with a small radius in the glass, thereby forming a compressive stress layer on the surface of the glass and a tensile stress layer inside the glass. Compared to the glass-ceramics before strengthening, the occurrence of ion exchange will cause the composition of the compressive stress layer to change. Since the ion exchange depth is usually less than or equal to the thickness of the compressive stress layer, the composition of the tensile stress layer inside the glass will not change, that is, the composition of the tensile stress layer is the same as that of the glass-ceramics before strengthening.
[0166] The tensile stress layer has an upper boundary that is spaced a certain distance from the upper surface of the strengthened microcrystalline glass and a lower boundary that is spaced a certain distance from the lower surface of the strengthened glass. A curve drawn with the magnitude of the tensile stress at a point on a line segment in the tensile stress layer that is perpendicular to the upper boundary and the lower boundary and whose upper and lower endpoints fall on the upper boundary and the lower boundary respectively as the Y-axis and the distance of the corresponding point from the upper boundary as the X-axis is recorded as a tensile stress curve. The ratio of the definite integral of the tensile stress curve to the thickness of the strengthened microcrystalline glass is recorded as the tensile stress linear density, which is the ratio of the sum of the tensile stresses of the strengthened microcrystalline glass measured by the SLP-2000 stress meter to the glass thickness.
[0167] |CT_AV|: Absolute value of average tensile stress, specifically refers to the absolute value of the average value of all tensile stresses in the tensile stress layer, obtained by SLP-2000 stress meter test.
[0168] DOL_0: Depth of compressive stress layer, or depth of compressive stress layer, refers to the distance from any surface of microcrystalline glass to the position close to the surface where the compressive stress is zero, obtained by SLP-2000 stress meter test.
[0169] |CT_CV|: The maximum central tensile stress or the absolute value of the maximum tensile stress, specifically the maximum value of all tensile stresses in the tensile stress layer, obtained by testing with the SLP-2000 stress meter.
[0170] Surface compressive stress: surface CS. After chemical strengthening of glass ceramics, the alkali metal ions with smaller surface radius are replaced by alkali metal ions with larger radius. Due to the crowding effect of the alkali metal ions with larger radius, compressive stress is generated on the glass surface, which is called surface compressive stress. Surface CS is obtained by SLP-2000 stress meter test.
[0171] CS_50: compressive stress at a depth of 50 μm from the glass surface.
[0172] CS_100: compressive stress at a depth of 100 μm from the glass surface.
[0173] Transmittance: The ratio of the radiant energy that is projected and passes through an object to the total radiant energy that is projected onto the object during the process of the incident light flux leaving from the illuminated surface or the incident surface of the medium to the other side.
[0174] Refractive index: The ratio of the speed of light in a vacuum to the speed of light in the medium.
[0175] In the embodiments and comparative examples of the present invention, the transmittance of the glass-ceramics at a wavelength of 550 nm is the average transmittance of multiple glass samples of the same batch measured at a wavelength of 550 nm. At least 5 samples of each batch of glass-ceramics are taken for testing.
[0176] SOC: Photoelastic coefficient. Photoelasticity mainly refers to the phenomenon of anisotropy and birefringence of transparent materials after being subjected to force. The value of the residual stress (MPa) inside the material can be obtained by measuring the photoelastic coefficient and birefringence.
[0177] Instruments and test methods
[0178] Glass thickness: Determined by micrometer test. The thickness change of glass-ceramics before and after chemical strengthening is very small and can be ignored.
[0179] Crystal content test: The microcrystalline glass sample is tested by an X-ray diffractometer to obtain an XRD diffraction peak curve, and then the X-ray diffractometer (Shimadzu XRD-6000) test result file (RAW format) is imported into the X-ray diffraction data Rietveld refinement software (such as Gsas, Fullprof, Maud), and the crystal content in the microcrystalline glass sample can be obtained by fitting and calculating. The ratio of the fitted crystal phase peak area to the fitted total peak area is the crystal content. The X-ray diffractometer used in the present invention is Shimadzu's XRD-6000, and the diffraction angle range used in the test is 2θ=10~50°, the scanning speed is 6° / min, the operating voltage is 40KV, and the operating current is 30mA.
[0180] The method for obtaining the average grain size is: using an X-ray diffractometer to test the microcrystalline glass sample, and using the Scherrer formula D = Kλ / (βcosθ) for the result data obtained from the XRD test, where λ is the X-ray wavelength, β is the peak half-height width, and K = 0.89, the average grain size can be obtained.
[0181] Transmittance test: According to the standard of GB / T 7962.12-2010 Test method for colorless optical glass Part 12: Spectral transmittance, the transmittance of microcrystalline glass is tested using professional testing instruments. The testing instruments used in the present invention are Konica Minolta CM-3600A spectrophotometer and Shimadzu UV-visible spectrophotometer UV-2600.
[0182] Surface compressive stress (surface CS), CS_50, CS_100, CT_AV, CT_CV, DOL_0 tests: Use Japan Luceo (Japan Orihara) stress meter SLP-2000 for testing, light source wavelength is 518nm, SOC = 25.5 (nm / cm) / MPa, refractive index = 1.54, exposure time: 300 μ sec.
[0183] When testing the surface CS, CS_50, CS_100, CT_AV, CT_CV, DOL_0, it is necessary to drop the special refractive liquid on the stress meter, then wipe the tempered micro-ceramic glass product clean, place it on the test path, and test its value. The refractive index of the refractive liquid used by SLP-2000 is 1.51.
[0184] CT_LD is related to the thickness of the glass sheet, the strengthening depth and the average tensile stress, and can be used to evaluate the drop resistance of the glass sheet. The CT_LD satisfies the following formula:
[0185]
[0186] Wherein d represents the thickness of the microcrystalline glass sheet (the glass thickness in the following embodiments and comparative examples of the present invention is 0.7 mm), unit: mm; DOL_0 represents the depth of the compressive stress layer, unit: μm; CT_AV represents the internal average tensile stress, and its absolute value is taken in calculation, unit: MPa.
[0187] Differential Scanning Calorimetry (DSC) test: The sample was ground and passed through a 200-mesh sieve; the test conditions were: room temperature to 1000°C, 10°C / min heating rate; the test instrument was Mettler-Toledo TGA / DSC3+ thermogravimetric and synchronous thermal analyzer, and the results were as follows: Figure 1 .
[0188] Average sandpaper drop resistance height: The value obtained by dividing the sum of the sandpaper drop resistance heights measured for multiple glass samples by the number of samples measured, which is used to characterize the glass's resistance to contact surface cracking.
[0189] Take at least 10 samples from each batch for testing, and the average sandpaper drop height
[0190]
[0191] Where n is the number of glass samples tested in each batch, and hi is the sandpaper drop resistance height of a single sample tested.
[0192] Among them, the test method for the sample's resistance to sandpaper drop height is:
[0193] Step 1: Stick the glass sample to be tested with a length, width and thickness of 158.8mm×72.8mm×0.7mm on the front of the 200g model machine;
[0194] Step 2: Place the model machine on the Green Figure LT-SKDL-CD drop machine, with the glass sample facing the sandpaper, and drop it from a certain drop height, impacting the 80 mesh / 120 mesh / 180 mesh sandpaper located directly below the model machine, simulating the normal drop posture of a mobile phone.
[0195] If the glass sample does not break, the drop height of the model machine is increased in a certain pattern. For example, the drop height starts from 0.4m, and the sample is dropped once. If it does not break, the drop height is increased by 0.1m each time until the glass sample breaks.
[0196] Step 3: The last drop height of the glass sample when it breaks is recorded as the anti-sandpaper drop height. For example, if the drop height when it breaks is 0.5m, the anti-sandpaper drop height of the sample is 0.4m.
[0197] The method for preparing the tempered glass-ceramics of the present invention comprises the following steps:
[0198] (1) Preparation of substrate glass:
[0199] Mix the ingredients according to the formula for 30 minutes, add a clarifier after mixing, and melt in a platinum crucible at 1400-1650°C for 5 hours, then pour into a molding mold for molding, cool to 900°C, put into an annealing furnace at 450-600°C, preferably 450-550°C, anneal for 6-240 hours, preferably anneal for 6-120 hours, and then cool to room temperature with the furnace to obtain the substrate glass.
[0200] The clarifier can be any one or more substances selected from NaCl, Sb2O3, As2O3, nitrate, sulfate, etc., and the mass ratio of the clarifier added to the base glass raw material is 0.10-1.00wt%, that is, the amount of the clarifier accounts for 0.10-1.00wt% of the total amount of the base glass raw material.
[0201] (2) Preparation of glass-ceramics:
[0202] Transparent microcrystalline glass bricks can be prepared by subjecting the substrate glass to the following nucleation treatment and crystallization treatment in sequence.
[0203] When performing nucleation treatment, the temperature is increased to the nucleation temperature at a heating rate of 5 to 20°C / min, preferably 10°C / min, the nucleation temperature is 500 to 700°C, and the nucleation treatment time is 10 to 1440 minutes. When performing crystallization treatment, the temperature is increased to the crystallization temperature at a heating rate of 5 to 20°C / min, preferably 10°C / min, the crystallization temperature is 640 to 750°C, and the crystallization treatment time is 5 to 1440 minutes. The nucleation treatment time here refers to the time of keeping the crystallization furnace warm after heating it to the set nucleation temperature at the set heating rate. The crystallization treatment time here refers to the time of keeping the crystallization furnace warm after heating it to the set crystallization temperature at the set heating rate.
[0204] (3) Sample cold processing:
[0205] The microcrystalline glass bricks obtained in step (2) are subjected to cold working treatment, wherein the cold working treatment includes slicing treatment. Before slicing treatment, the microcrystalline glass bricks can be shaped, and after slicing treatment, they can be CNC treated, ground, and polished in sequence, or after slicing treatment, at least one of CNC treatment, grinding, and polishing treatment is selected to perform glass sheet modification treatment to obtain microcrystalline glass samples of desired sizes, such as polished sheets with length, width, and thickness of 50 mm×50 mm×0.7 mm, 158.8 mm×72.8 mm×0.7 mm, etc.
[0206] (4) Chemical strengthening:
[0207] The obtained microcrystalline glass sample (i.e., polished piece) is chemically strengthened in a pure sodium salt or lithium-sodium-potassium mixed salt bath at 380-550°C for 1-24 hours. The sodium ions in the salt bath are provided by any one or more of sodium nitrate, sodium sulfate and sodium carbonate, the potassium ions are provided by any one of potassium nitrate, potassium sulfate and potassium carbonate, and the lithium ions are provided by one or more of lithium nitrate, lithium sulfate and lithium carbonate. The present invention preferably uses a mixed salt composed of lithium nitrate, sodium nitrate and potassium nitrate for chemical strengthening treatment.
[0208] In some embodiments, the strengthening salt bath of the present invention comprises 0.1-100 wt % NaNO 3 and 0-99.9 wt % KNO 3 , and LiNO 3 is added in an amount of 0-10 wt % relative to the total weight of the salt bath.
[0209] The strengthened microcrystalline glass and the preparation method of the present invention are described in detail below through specific embodiments.
[0210] Example
[0211] Taking Example 3 as an example, the specific preparation process is as follows:
[0212] According to the composition ratio of substrate glass E shown in Table 1, weigh the total amount of various raw material powders to be 1000g, add 5g of clarifier (NaCl), mix with a mixer for 30 minutes, and melt in a platinum crucible at 1650℃ for 5 hours, then pour into a molding mold for molding, cool to 900℃, put into a 480℃ annealing furnace for annealing for 12 hours, and then cool to room temperature with the furnace (reduced to room temperature at a rate of about 5℃ / min) to obtain a substrate glass sample brick; the preparation method of the substrate glass in other embodiments is the same as that in Example 3, wherein the formula ingredient ratios of the substrate glass in Examples 1-6 and Comparative Examples 1-7 correspond to the ingredient letters in Table 1, respectively, and are specifically described in Tables 2-2 and 2-1.
[0213] The substrate glass was placed in an annealing furnace for nucleation and crystallization treatment. The whole heating rate was set at 10℃ / min, and the temperature was raised from room temperature to 545℃, and kept at 545℃ for 4 hours for nucleation treatment; then the temperature was raised to 675℃, and kept at 675℃ for 90 minutes for crystallization treatment; then the temperature was cooled to room temperature with the furnace to obtain a microcrystalline glass brick.
[0214] After shaping, slicing, CNC, flat grinding and polishing, the glass-ceramic sample bricks are obtained to obtain glass-ceramic samples of desired sizes, such as polished sheets with a length, width and thickness of 50mm×50mm×0.7mm, 158.8mm×72.8mm×0.7mm, etc.
[0215] According to the salt bath ratio shown in Table 2-2, 700g NaNO3, 300g KNO3, and 0.3g LiNO3 (70wt% NaNO3 + 30wt% KNO3 + 0.03wt% LiNO3, where 0.03wt% LiNO3 refers to the mass ratio of the additional LiNO3 added relative to the total amount of the mixed salt composed of Na NO3 and KNO3) were weighed and placed in a crucible, and melted into a liquid state in a strengthening furnace at a temperature of 480°C. The obtained polished sheet was placed in a molten salt bath and strengthened at 480°C for 7 hours to perform a strengthening treatment to obtain a strengthened microcrystalline glass sheet.
[0216] The obtained strengthened microcrystalline glass sheet was subjected to performance testing. After stress testing with SLP-2000, a whole machine drop test with sandpaper of different mesh sizes was performed. The results are shown in Table 2-2.
[0217] Tables 2-1 and 2-2 show the specific conditions for strengthening the glasses of comparative examples 1-7 and embodiments 1-6, including the salt bath mass ratio, salt bath temperature and salt bath time (except that comparative example 1 was subjected to a secondary strengthening treatment (the strengthening salt baths used for the first and second strengthening treatments were referred to as "one strong salt bath" and "two strong salt baths", respectively), the other embodiments and comparative examples were only subjected to a single strengthening treatment); after different strengthening treatments were performed on the obtained different strengthened glass microcrystal samples, various stress tests and drop tests were performed, and the specific stress test data and drop test data are summarized in Tables 2-1 and 2-2, respectively.
[0218] It can be seen from comparative examples 1 to 7 in Table 2-1 that when the microcrystalline glass cannot simultaneously meet 1.01% ≥ Δα ≥ 0.65%, (CS_50 / DOL_0) ≥ 0.332×(surface CS / |CT_CV|), and DOL_0 ≥ 0.187t after strengthening, the average height of the whole machine falling with 80-mesh sandpaper is only between 0.88 and 1.15 m.
[0219] It can be seen from Examples 1 to 6 in Table 2-2 that the surface CS of the tempered microcrystalline glass of the present invention is greater than 270 MPa, within the range of 272-428 MPa; CS_50 is greater than 164 MPa, within the range of 164.44-245.83 MPa; CS_100 is greater than 59.55 MPa, within the range of 59.55-91.81 MPa; |CT_CV| is greater than 113 MPa, and |CT_CV| is specifically within the range of 113.54-145.86 MPa; |CT_AV| is greater than 85 MPa, within the range of 85.49-101.19 MPa; DOL_0 is greater than 130 μm, within the range of 130.60-151.57 μm; CT_LD is greater than 50000 MPa / mm, within the range of 50477.18-60721.55 MPa / mm. The characteristics of the strengthened microcrystalline glass of the present invention satisfy 1.01% ≥ Δα ≥ 0.65%, (CS_50 / DOL_0) ≥ 0.332×(surface CS / |CT_CV|), and DOL_0 ≥ 0.187t. In the whole machine drop test with 80-grit sandpaper, the average sandpaper drop resistance height of the strengthened microcrystalline glass can reach more than 1.31m. It can be seen from Tables 2-1 and 2-2 that for the same glass sample, the larger the sandpaper mesh number, the larger the average drop height. The larger the sandpaper mesh number, the smaller the coated corundum particles and the shallower the puncture depth.
[0220] Furthermore, the present invention Figure 1 This is the DSC graph of the substrate glass in Example 3 of the present invention (glass E composition), which is heated to 1000°C at a heating rate of 10°C / min in nitrogen. It can be seen from the graph that the nucleation temperature of the substrate glass of this formula is between 530 and 550°C, and the crystallization temperature is between 670 and 700°C.
[0221] Figure 2 This is a transmittance curve of the microcrystalline glass of Example 3 (glass E composition) tested by Shimadzu UV-2600 UV-visible spectrophotometer at 200nm~1000nm. It can be seen from the figure that: in the visible light wavelength, the microcrystalline glass of the present invention has a higher transmittance and better transparency.
[0222] Figure 3 It is the X-ray diffraction pattern of the microcrystalline glass of Example 3 of the present invention (glass E composition). From the diffraction pattern, it can be seen that Example 3 obtains: the microcrystalline glass of the present invention mainly contains petalite and lithium disilicate crystal phases.
[0223] Table 1: Formulation, heat treatment, crystal phase composition and transmittance of glass-ceramics
[0224]
[0225]
[0226] Table 2-1
[0227]
[0228]
[0229] Table 2-2
[0230]
[0231]
[0232]
[0233] Note: Since the upper limit of the drop test machine used for drop test is 2.5m, if the glass is still not broken after the drop test at the upper limit test height, it is judged that the average sandpaper drop height of the glass is greater than 2.5m.
Claims
1. A terminal product, characterized in that: The terminal product includes a strengthened microcrystalline glass, the strengthened microcrystalline glass contains a petalite crystal phase and a lithium disilicate crystal phase, the strengthened microcrystalline glass has a compressive stress layer formed by chemical strengthening on the surface and a tensile stress layer inside; The strengthened glass-ceramics meets the following requirements: DOL_0≥0.187t, t is the thickness of the strengthened glass-ceramics, preferably DOL_0≥0.195t, more preferably DOL_0≥0.200t; 1.01%≥Δα>0.66%,Δα=5×10 -5 ×|CT_AV|+0.0026; The tensile stress linear density CT_LD is 45000MPa / mm~90000MPa / mm; |CT_CV| is 50MPa~210MPa; in: CT_AV: average tensile stress in the tensile stress layer, in MPa; CT_CV: maximum tensile stress in the tensile stress layer, in MPa; DOL_0: Depth of compressive stress layer, in μm.
2. The terminal product according to claim 1, characterized in that: The strengthened glass-ceramics meets the following requirements: |CT_AV| is greater than 80.63MPa; and / or, |CT_CV| is greater than 113MPa.
3. The terminal product according to any one of claims 1-2, characterized in that: The strengthened microcrystalline glass satisfies: CS_50 is 100MPa to 400MPa; and / or CS_100 is 20MPa to 150MPa.
4. The terminal product according to any one of claims 1 to 3, characterized in that: The strengthened glass-ceramics meets the following requirements: CT_LD is greater than 50000 MPa / mm; and / or, |CT_AV| is greater than 85 MPa, preferably, |CT_AV| is 85.49 MPa-101.19 MPa; and / or, |CT_CV| is 113.54 MPa-145.86 MPa; and / or, CS_50 is greater than 164 MPa, preferably CS_50 is 164.44 MPa-245.83 MPa; and / or, CS_100 is greater than 59.55 MPa, and preferably CS_100 is 59.55 MPa-91.81 MPa.
5. The terminal product according to any one of claims 1 to 4, characterized in that: The strengthened glass-ceramics meets the following requirements: (CS_50 / DOL_0)≥0.332×(surface CS / |CT_CV|); in: Surface CS: surface compressive stress, in MPa; CS_50: compressive stress at a depth of 50 μm from the glass surface, in MPa; CT_AV: average tensile stress in the tensile stress layer, in MPa; CT_CV: maximum tensile stress in the tensile stress layer, in MPa; and DOL_0: depth of compressive stress layer, in μm; Preferably, (CS_50 / DOL_0) / (surface CS / |CT_CV|)≥0.472, more preferably, (CS_50 / DOL_0) / (surface CS / |CT_CV|)≥0.
552.
6. The terminal product according to any one of claims 1 to 5, characterized in that: The strengthened microcrystalline glass satisfies: the surface CS is 200 to 680 MPa, preferably the surface CS is greater than 270 MPa, and more preferably the surface CS is 272 MPa-428 MPa.
7. The terminal product according to any one of claims 1 to 6, characterized in that: The strengthened glass-ceramics meets the following requirements: 1.01%≥Δα≥0.69%.
8. The terminal product according to any one of claims 1 to 7, characterized in that: In the strengthened glass-ceramics, the total content of the petalite crystal phase and the lithium disilicate crystal phase is greater than 75 wt %, preferably greater than or equal to 79 wt %, and more preferably 79 wt % to 97 wt %.
9. The terminal product according to any one of claims 1 to 8, characterized in that: In the strengthened glass-ceramics, the average size of the grains is 10nm-50nm, preferably 10nm-30nm, and more preferably 10nm-20nm.
10. The terminal product according to any one of claims 1 to 9, characterized in that: At a thickness of 0.7 mm, the strengthened microcrystalline glass is transparent. Preferably, for light of a wavelength of 550 nm, the transmittance of the strengthened microcrystalline glass is not less than 90.00%.
11. The terminal product according to any one of claims 1 to 10, characterized in that: In the tensile stress layer of the strengthened glass-ceramics: The weight percentage of SiO2 is 65.00% to 75.00%, the weight percentage of Al2O3 is 5.00% to 10.00%, the weight percentage of P2O5 is 1.00% to 5.00%, the weight percentage of ZrO2 is 1.00% to 10.00%, and the weight percentage of Li2O is 5.00% to 15.00%.
12. The terminal product according to claim 11, characterized in that: The tensile stress layer of the strengthened glass-ceramics further contains K2O. Preferably, the mass percentage of K2O in the tensile stress layer of the strengthened glass-ceramics is 0.10% to 3.00%, preferably 0.10% to 0.50%, and more preferably 0.13% to 0.37%; and / or, The tensile stress layer of the strengthened glass-ceramics further contains CaO. Preferably, the mass percentage of CaO in the tensile stress layer of the strengthened glass-ceramics is 0.10% to 3.00%, preferably 0.50% to 1.00%, and more preferably 0.77% to 0.98%.
13. The terminal product according to claim 11 or 12, characterized in that: The tensile stress layer of the strengthened glass-ceramics further contains 0-5.00% by weight of Na2O, preferably 0-1.00% by weight of Na2O, more preferably 0.31%-1.00% or 0.06%-0.31% by weight of Na2O; and / or, The tensile stress layer of the strengthened microcrystalline glass further contains 0 to 4.00% by mass of B2O3, preferably 0.10% to 1.00% by weight, and more preferably 0.21% to 0.91% by weight of B2O3.
14. The terminal product according to any one of claims 11 to 13, characterized in that: In the tensile stress layer of the strengthened glass-ceramics: The weight percentage of SiO2 is 68.00% to 72.00%, preferably 70.00% to 72.00%, more preferably 70.06% to 71.65%; and / or, The weight percentage of Al2O3 is 6.00% to 10.00%, preferably 6.00% to 8.50%, more preferably 7.00% to 8.30%; and / or, The weight percentage of P2O5 is 1.00% to 3.00%, preferably 1.50% to 3.00%, more preferably 2.00% to 2.80%; and / or, The weight percentage of ZrO2 is 2.00% to 8.00%, preferably 5.00% to 7.00%, more preferably 5.40% to 6.60%; and / or, The weight percentage of Li2O is 8.00% to 13.00%, preferably 9.00% to 12.00%, and more preferably 10.00% to 11.50%.
15. The terminal product according to any one of claims 1 to 14, characterized in that: When the tempered glass-ceramics is subjected to a sandpaper drop resistance test using 80-grit sandpaper at a thickness of 0.7 mm, the average sandpaper drop resistance height of the tempered glass-ceramics is 1.30 to 1.80 m; and / or, When the tempered glass-ceramics is subjected to a sandpaper drop resistance test using 120-grit sandpaper at a thickness of 0.7 mm, the average sandpaper drop resistance height of the tempered glass-ceramics is greater than 2.00 m; and / or, At a thickness of 0.7 mm, a sandpaper drop resistance test was performed on the strengthened microcrystalline glass using 180-grit sandpaper, and the average sandpaper drop resistance height of the strengthened microcrystalline glass was greater than 2.50 m.
16. The terminal product according to any one of claims 1 to 15, characterized in that: The tempered microcrystalline glass is used as a protective cover plate of a terminal product. Preferably, the terminal product is a smart terminal product, and more preferably, the terminal product includes a mobile phone.
17. A strengthened glass-ceramic, characterized in that: The strengthened microcrystalline glass contains a petalite crystal phase and a lithium disilicate crystal phase, and the strengthened microcrystalline glass has a compressive stress layer formed by chemical strengthening on the surface and a tensile stress layer inside; The strengthened glass-ceramics meets the following requirements: DOL_0≥0.187t, t is the thickness of the strengthened glass-ceramics, preferably DOL_0≥0.195t, more preferably DOL_0≥0.200t; 1.01%≥Δα>0.66%,Δα=5×10 -5 ×|CT_AV|+0.0026; The tensile stress linear density CT_LD is 45000MPa / mm~90000MPa / mm; |CT_CV| is 50MPa~210MPa; in: CT_AV: average tensile stress in the tensile stress layer, in MPa; CT_CV: maximum tensile stress in the tensile stress layer, in MPa; DOL_0: Depth of compressive stress layer, in μm.
18. The tempered glass-ceramics according to claim 17, characterized in that: The strengthened glass-ceramics meets the following requirements: |CT_AV| is greater than 80.63MPa; and / or, |CT_CV| is greater than 113MPa.
19. The strengthened glass-ceramics according to any one of claims 17 to 18, characterized in that: The strengthened microcrystalline glass satisfies: CS_50 is 100MPa to 400MPa; and / or CS_100 is 20MPa to 150MPa.
20. The strengthened glass-ceramics according to any one of claims 17 to 19, characterized in that: The strengthened glass-ceramics meets the following requirements: CT_LD is greater than 50000 MPa / mm; and / or, |CT_AV| is greater than 85 MPa, preferably, |CT_AV| is 85.49 MPa-101.19 MPa; and / or, |CT_CV| is 113.54MPa-145.86MPa; and / or, CS_50 is greater than 164 MPa, preferably CS_50 is 164.44 MPa-245.83 MPa; and / or, CS_100 is greater than 59.55 MPa, and preferably CS_100 is 59.55 MPa-91.81 MPa.
21. The strengthened glass-ceramics according to any one of claims 17 to 20, characterized in that: The strengthened glass-ceramics meets the following requirements: (CS_50 / DOL_0)≥0.332×(surface CS / |CT_CV|); in: Surface CS: surface compressive stress, in MPa; CS_50: compressive stress at a depth of 50 μm from the glass surface, in MPa; CT_AV: average tensile stress in the tensile stress layer, in MPa; CT_CV: maximum tensile stress in the tensile stress layer, in MPa; and DOL_0: depth of compressive stress layer, in μm; Preferably, (CS_50 / DOL_0) / (surface CS / |CT_CV|)≥0.472, more preferably, (CS_50 / DOL_0) / (surface CS / |CT_CV|)≥0.
552.
22. The strengthened glass-ceramics according to any one of claims 17 to 21, characterized in that: The strengthened microcrystalline glass satisfies: the surface CS is 200-680 MPa, preferably the surface CS is greater than 270 MPa, and more preferably the surface CS is 272 MPa-428 MPa.
23. The strengthened glass-ceramics according to any one of claims 17 to 22, characterized in that: The strengthened glass-ceramics meets the following requirements: 1.01%≥Δα≥0.69%.
24. The strengthened glass-ceramics according to any one of claims 17 to 23, characterized in that: In the strengthened glass-ceramics, the total content of the petalite crystal phase and the lithium disilicate crystal phase is greater than 75 wt %, preferably greater than or equal to 79 wt %, and more preferably 79 wt % to 97 wt %.
25. The strengthened glass-ceramics according to any one of claims 17 to 24, characterized in that: In the strengthened glass-ceramics, the average size of the grains is 10nm-50nm, preferably 10nm-30nm, and more preferably 10nm-20nm.
26. The strengthened glass-ceramics according to any one of claims 17 to 25, characterized in that: At a thickness of 0.7 mm, the strengthened microcrystalline glass is transparent. Preferably, for light of a wavelength of 550 nm, the transmittance of the strengthened microcrystalline glass is not less than 90.00%.
27. The strengthened glass-ceramics according to any one of claims 17 to 26, characterized in that: In the tensile stress layer of the strengthened glass-ceramics: The weight percentage of SiO2 is 65.00% to 75.00%, the weight percentage of Al2O3 is 5.00% to 10.00%, the weight percentage of P2O5 is 1.00% to 5.00%, the weight percentage of ZrO2 is 1.00% to 10.00%, and the weight percentage of Li2O is 5.00% to 15.00%.
28. The tempered glass-ceramics according to claim 27, characterized in that: The tensile stress layer of the strengthened glass-ceramics further contains K2O. Preferably, the mass percentage of K2O in the tensile stress layer of the strengthened glass-ceramics is 0.10% to 3.00%, preferably 0.10% to 0.50%, and more preferably 0.13% to 0.37%; and / or, The tensile stress layer of the strengthened glass-ceramics further contains CaO. Preferably, the mass percentage of CaO in the tensile stress layer of the strengthened glass-ceramics is 0.10% to 3.00%, preferably 0.50% to 1.00%, and more preferably 0.77% to 0.98%.
29. The tempered glass-ceramics according to claim 27 or 28, characterized in that: The tensile stress layer of the strengthened glass-ceramics further contains 0-5.00% by weight of Na2O, preferably 0-1.00% by weight of Na2O, more preferably 0.31%-1.00% or 0.06%-0.31% by weight of Na2O; and / or, The tensile stress layer of the strengthened microcrystalline glass further contains 0 to 4.00% by mass of B2O3, preferably 0.10% to 1.00% by weight, and more preferably 0.21% to 0.91% by weight of B2O3.
30. The strengthened glass-ceramics according to any one of claims 27 to 29, characterized in that: In the tensile stress layer of the strengthened glass-ceramics: The weight percentage of SiO2 is 68.00% to 72.00%, preferably 70.00% to 72.00%, more preferably 70.06% to 71.65%; and / or, The weight percentage of Al2O3 is 6.00% to 10.00%, preferably 6.00% to 8.50%, more preferably 7.00% to 8.30%; and / or, The weight percentage of P2O5 is 1.00% to 3.00%, preferably 1.50% to 3.00%, more preferably 2.00% to 2.80%; and / or, The weight percentage of ZrO2 is 2.00% to 8.00%, preferably 5.00% to 7.00%, more preferably 5.40% to 6.60%; and / or, The weight percentage of Li2O is 8.00% to 13.00%, preferably 9.00% to 12.00%, and more preferably 10.00% to 11.50%.
31. The strengthened glass-ceramics according to any one of claims 17 to 30, characterized in that: When the tempered glass-ceramics is subjected to a sandpaper drop resistance test using 80-grit sandpaper at a thickness of 0.7 mm, the average sandpaper drop resistance height of the tempered glass-ceramics is 1.30 to 1.80 m; and / or, When the tempered glass-ceramics is subjected to a sandpaper drop resistance test using 120-grit sandpaper at a thickness of 0.7 mm, the average sandpaper drop resistance height of the tempered glass-ceramics is greater than 2.00 m; and / or, At a thickness of 0.7 mm, a sandpaper drop resistance test was performed on the strengthened microcrystalline glass using 180-grit sandpaper, and the average sandpaper drop resistance height of the strengthened microcrystalline glass was greater than 2.50 m.
32. A strengthened glass-ceramic, characterized in that: The strengthened microcrystalline glass contains a petalite crystal phase and a lithium disilicate crystal phase, and the strengthened microcrystalline glass has a compressive stress layer formed by chemical strengthening on the surface and a tensile stress layer inside; The strengthened glass-ceramics meets the following requirements: DOL_0≥0.187t, t is the thickness of the strengthened glass-ceramics, preferably DOL_0≥0.195t, more preferably DOL_0≥0.200t; The tensile stress linear density CT_LD is 45000MPa / mm~90000MPa / mm; |CT_CV| is 50MPa~210MPa; |CT_AV| is greater than 85MPa; in: CT_AV: average tensile stress in the tensile stress layer, in MPa; CT_CV: maximum tensile stress in the tensile stress layer, in MPa; DOL_0: Depth of compressive stress layer, in μm.
33. The tempered glass-ceramics according to claim 32, characterized in that: The strengthened glass-ceramics meets the following requirements: |CT_CV| is greater than 113MPa; where CT_CV: maximum tensile stress in the tensile stress layer, in MPa.
34. The strengthened glass-ceramic according to any one of claims 32 to 33, characterized in that: The strengthened microcrystalline glass satisfies: CS_50 is 100MPa to 400MPa; and / or CS_100 is 20MPa to 150MPa.
35. The strengthened glass-ceramics according to any one of claims 32 to 34, characterized in that: The strengthened glass-ceramics meets the following requirements: CT_LD is greater than 50000 MPa / mm; and / or, |CT_CV| is 113.54MPa-145.86MPa; and / or, CS_50 is greater than 164 MPa, preferably CS_50 is 164.44 MPa-245.83 MPa; and / or, CS_100 is greater than 59.55 MPa, and preferably CS_100 is 59.55 MPa-91.81 MPa.
36. The strengthened glass-ceramics according to any one of claims 32 to 35, characterized in that: The strengthened glass-ceramics meets the following requirements: (CS_50 / DOL_0)≥0.332×(surface CS / |CT_CV|); in: Surface CS: surface compressive stress, in MPa; CS_50: compressive stress at a depth of 50 μm from the glass surface, in MPa; CT_AV: average tensile stress in the tensile stress layer, in MPa; CT_CV: maximum tensile stress in the tensile stress layer, in MPa; and DOL_0: depth of compressive stress layer, in μm; Preferably, (CS_50 / DOL_0) / (surface CS / |CT_CV|)≥0.472, more preferably, (CS_50 / DOL_0) / (surface CS / |CT_CV|)≥0.
552.
37. The strengthened glass-ceramics according to any one of claims 32 to 36, characterized in that: The strengthened microcrystalline glass satisfies: the surface CS is 200-680 MPa, preferably the surface CS is greater than 270 MPa, and more preferably the surface CS is 272 MPa-428 MPa.
38. The strengthened glass-ceramics according to any one of claims 32 to 37, characterized in that: The strengthened glass-ceramics meets the following requirements: 1.01%≥Δα≥0.69%, Δα=5×10 -5 ×|CT_AV|+0.0026; where: CT_AV: average tensile stress in the tensile stress layer, in MPa; preferably, |CT_AV| is 85.49MPa-101.19MPa.
39. The strengthened glass-ceramics according to any one of claims 32 to 38, characterized in that: In the strengthened glass-ceramics, the total content of the petalite crystal phase and the lithium disilicate crystal phase is greater than 75 wt %, preferably greater than or equal to 79 wt %, and more preferably 79 wt % to 97 wt %.
40. The strengthened glass-ceramic according to any one of claims 32 to 39, characterized in that: In the strengthened glass-ceramics, the average size of the grains is 10nm-50nm, preferably 10nm-30nm, and more preferably 10nm-20nm.
41. The strengthened glass-ceramics according to any one of claims 32 to 40, characterized in that: At a thickness of 0.7 mm, the strengthened microcrystalline glass is transparent to light of a wavelength of 550 nm. Preferably, the transmittance of the strengthened microcrystalline glass is not less than 90.00%.
42. The strengthened glass-ceramic according to any one of claims 32 to 41, characterized in that: In the tensile stress layer of the strengthened microcrystalline glass: the weight percentage of SiO2 is 65.00% to 75.00%, the weight percentage of Al2O3 is 5.00% to 10.00%, the weight percentage of P2O5 is 1.00% to 5.00%, the weight percentage of ZrO2 is 1.00% to 10.00%, and the weight percentage of Li2O is 5.00% to 15.00%.
43. The strengthened glass-ceramics according to claim 42, characterized in that: The tensile stress layer of the strengthened glass-ceramics further contains K2O. Preferably, the mass percentage of K2O in the tensile stress layer of the strengthened glass-ceramics is 0.10% to 3.00%, preferably 0.10% to 0.50%, and more preferably 0.13% to 0.37%; and / or, The tensile stress layer of the strengthened glass-ceramics further contains CaO. Preferably, the mass percentage of CaO in the tensile stress layer of the strengthened glass-ceramics is 0.10% to 3.00%, preferably 0.50% to 1.00%, and more preferably 0.77% to 0.98%.
44. The tempered glass-ceramics according to claim 42 or 43, characterized in that: The tensile stress layer of the strengthened glass-ceramics further contains 0-5.00% by weight of Na2O, preferably 0-1.00% by weight of Na2O, more preferably 0.31%-1.00% or 0.06%-0.31% by weight of Na2O; and / or, The tensile stress layer of the strengthened microcrystalline glass further contains 0 to 4.00% by mass of B2O3, preferably 0.10% to 1.00% by weight, and more preferably 0.21% to 0.91% by weight of B2O3.
45. The strengthened glass-ceramic according to any one of claims 42 to 44, characterized in that: In the tensile stress layer of the strengthened glass-ceramics: The weight percentage of SiO2 is 68.00% to 72.00%, preferably 70.00% to 72.00%, more preferably 70.06% to 71.65%; and / or, The weight percentage of Al2O3 is 6.00% to 10.00%, preferably 6.00% to 8.50%, more preferably 7.00% to 8.30%; and / or, The weight percentage of P2O5 is 1.00% to 3.00%, preferably 1.50% to 3.00%, more preferably 2.00% to 2.80%; and / or, The weight percentage of ZrO2 is 2.00% to 8.00%, preferably 5.00% to 7.00%, more preferably 5.40% to 6.60%; and / or, The weight percentage of Li2O is 8.00% to 13.00%, preferably 9.00% to 12.00%, and more preferably 10.00% to 11.50%.
46. The strengthened glass-ceramics according to any one of claims 32 to 45, characterized in that: When the tempered glass-ceramics is subjected to a sandpaper drop resistance test using 80-grit sandpaper at a thickness of 0.7 mm, the average sandpaper drop resistance height of the tempered glass-ceramics is 1.30 to 1.80 m; and / or, When the tempered glass-ceramics is subjected to a sandpaper drop resistance test using 120-grit sandpaper at a thickness of 0.7 mm, the average sandpaper drop resistance height of the tempered glass-ceramics is greater than 2.00 m; and / or, At a thickness of 0.7 mm, a sandpaper drop resistance test was performed on the strengthened microcrystalline glass using 180-grit sandpaper, and the average sandpaper drop resistance height of the strengthened microcrystalline glass was greater than 2.50 m.
47. A terminal product, characterized in that: The terminal product comprises the tempered microcrystalline glass as described in any one of claims 32-46, preferably the tempered microcrystalline glass is used as a protective cover plate of the terminal product, more preferably the terminal product is a smart terminal product, and further preferably the terminal product comprises a mobile phone.
48. A cover plate used in a mobile device or terminal product, characterized in that: The cover plate includes the strengthened micro-ceramic glass according to any one of claims 17 to 31 or includes the strengthened micro-ceramic glass according to any one of claims 32 to 46.
49. A mobile device, characterized in that: The mobile device comprises the strengthened microcrystalline glass according to any one of claims 17 to 31 or comprises the strengthened microcrystalline glass according to any one of claims 32 to 46, and the strengthened microcrystalline glass is preferably used as a protective cover in the mobile device.
50. The method for preparing the strengthened glass-ceramics according to any one of claims 17 to 31 or any one of claims 32 to 46, characterized in that: Including the following processes: (1) Preparation of substrate glass: After mixing various glass raw materials, adding a clarifier, melting and forming, and annealing to obtain the substrate glass; (2) Preparation of glass-ceramics: subjecting the glass substrate obtained in step (1) to nucleation and crystallization to obtain glass-ceramics; (3) cold working the glass-ceramics obtained in step (2) to obtain a polished sheet; and (4) The polished sheet obtained in step (3) is subjected to chemical strengthening treatment to obtain strengthened microcrystalline glass.
51. The preparation method according to claim 50, wherein: In step (1), the annealing temperature is 450 to 600° C., preferably 450 to 550° C., and the annealing time is 6 to 240 hours, preferably 6 to 120 hours.
52. The preparation method according to claim 50 or 51, wherein: In step (2), when the nucleation treatment is performed, the nucleation temperature is 500 to 700° C., preferably 540 to 570° C., and the nucleation treatment time is preferably 10 to 1440 min.
53. The preparation method according to any one of claims 50-52, wherein In the step (2), when the nucleation treatment is performed, the temperature is raised to the nucleation temperature at a heating rate of 5 to 20° C. / min, preferably at a heating rate of 10° C. / min.
54. The preparation method according to any one of claims 50 to 53, wherein In the step (2), when the crystallization treatment is performed, the crystallization temperature is 640 to 750° C., preferably 660 to 740° C., and may be 670 to 740° C., and the crystallization treatment time is preferably 5 to 1440 min.
55. The preparation method according to any one of claims 50 to 54, wherein In step (2), when the crystallization treatment is performed, the temperature is increased to the crystallization temperature at a temperature increase rate of 5 to 20° C. / min, preferably at a temperature increase rate of 10° C. / min.
56. The preparation method according to any one of claims 50 to 55, wherein In step (4), the polishing sheet obtained in step (3) is chemically strengthened in a pure sodium salt or lithium sodium potassium mixed salt bath at 380 to 550° C., and the strengthening time is preferably 1 to 24 hours.
57. The preparation method according to any one of claims 50 to 56, wherein In step (4), the sodium ions in the salt bath are provided by any one or more of sodium nitrate, sodium sulfate and sodium carbonate, the potassium ions are provided by any one or more of potassium nitrate, potassium sulfate and potassium carbonate, and the lithium ions are provided by one or more of lithium nitrate, lithium sulfate and lithium carbonate.
58. The preparation method according to claim 56 or 57, wherein: The composition of the lithium-sodium-potassium mixed salt bath is: based on the mass ratio, it contains 0.1-100wt% NaNO3 and 0-99.9wt% KNO3, and based on the total mass of NaNO3 and KNO3, it contains 0-10wt% LiNO3.
59. The preparation method according to claim 56 or 57, wherein: The composition of the lithium-sodium-potassium mixed salt bath is: in terms of mass ratio, it contains 30-95wt% NaNO3 and 5-70wt% KNO3, and relative to the total mass of NaNO3 and KNO3, it contains 0.01-1wt%, preferably 0.01-0.1wt%.
60. The production method according to any one of claims 50 to 59, wherein the chemical strengthening treatment in step (4) is performed 1 to 3 times.
61. The preparation method according to any one of claims 50 to 60, wherein in step (1), the clarifier is selected from any one or more of NaCl, Sb2O3, As2O3, nitrates, and sulfates, and preferably the mass percentage added to the glass is 0.10-1.00wt%, and more preferably the mass percentage added to the glass is 0.50-1.00wt%; and / or In the step (1), melt molding is performed at 1400 to 1650°C.
Citation Information
Patent Citations
Transparent microcrystalline glass, microcrystalline glass product and preparation method thereof
CN111099829A
Chemically strengthened microcrystalline glass and strengthening method
CN112608033A
Glass ceramic with ultrahigh bifurcation threshold value
CN113929308A
Glass composition, microcrystalline glass as well as preparation method and application of microcrystalline glass
CN114195393A
Glass ceramic, tempered glass and preparation method and application thereof
CN114671618A
Cited By
Weather-resistant microcrystalline glass, preparation method thereof, glass device, cover plate glass and electronic equipment
CN122145042A
A weather-resistant microcrystalline glass and its preparation method, glass devices, cover glass, and electronic devices.
CN122145042B